Sentimental Analysis – Detecting Tweets on Twitter (International Journal of Innovative Research in Computer Science & Technology, 2022)
As we all know social media is a growing  industry in the current world. People of every age are using  social media directly or indirectly. Millions of people are  share their thoughts on Twitter day by day. Every tweet has  its own characteristics and expressions. The technologies I  have used for analyzing the datasets of Twitter are data  mining and NLP with Python. After collecting the data, we  have trained it and made the tweets capable of testing, so it  can give us the proper sentimental output. This paper will  help us to understand the sentiment analysis techniques and  also helps us to extract sentiments from Twitter datasets.  The Twitter datasets collected from Kaggle and other  sources. In this paper, we have focused on the comparative  study of the different algorithms as well as on techniques.
Keywords: Twitter Data; Sentimental Analysis; NLP & Mining; Naive-Bayes; Python